Beyond the lab: future-proofing agriculture for climate resilience and stress management - Pehlivan, Necla; Altaf, Muhammad Tanveer; Emamverdian, Abolghassem; Ghorbani, Abazar (Frontiers in Plant Science, 2025)
Biotechnology has revolutionized the agricultural landscape, ushering in a new era of crop improvement. Biotechnological delivery innovations have driven significant advancements, from enhancing nutritional value and shelf life to developing stress-resistant varieties. Leveraging techniques like genome editing, RNA interference (RNAi), and omics approaches, the potential to generate tolerant crops, create beneficial germplasm, achieve higher crop yields, and enable targeted biomolecule delivery has been unlocked, leading to the establishment of novel, sustainable agricultural systems. This review synthesized 481 studies sourced from the Web of Science (WOS) database, reflecting the diversity of plant species, biotechnological approaches, and abiotic/biotic stress categories reported in the literature over the past three years. The findings focused on specific applications and implications of various technologies across different stress categories and plant types, providing a detailed perspective on stress tolerance mechanisms. Furthermore, the review highlights significant areas of controversy, including ethical concerns, debates, challenges, risks, socioeconomic impacts, and limitations associated with these technological advancements. As the world’s population surges and dietary demands evolve, biotechnology holds the key to assuring secure food supplies and promoting sustainable agricultural practices amidst the challenges brought about by climate change. This synthesis highlights the significant potential of biotechnological advancements in revolutionizing agriculture, facilitating the creation of resilient, adaptable, and sound systems capable of addressing the needs of a swiftly evolving world.